Structure of Passenger Transport Service Utility for Population - Nahornyi, Y. V; Ivanov, I. Y. (Science and Transport Progress, 2021)
Purpose. The research is aimed at the development of scientific and technological bases for determining the utility of passenger transport services for the population in the conditions of formation of phased quality management. Methodology. The structure of the utility of passenger transport services for the population is determined on the basis of developing a systematic representation of the characteristic impact of the perception of management decisions effectiveness for improving the quality of transport services on mobility. The account of complex system properties of city public passenger transport is realized by construction of interlevel interrelations and establishment of methodical regulations for coordinating the parameters of quality management of public transport service with the indicators of its utility perception. Findings. The presented logical sequence of population mobility formation is based on reproduction of the general conditions of increasing transport service utility due to step-by-step realization of control actions that makes it possible to establish conditions of their expediency and parameterization. A model of marginal utility has been developed to qualitatively assess the technological utility of urban public passenger transport. It is presented in the form of a category that reproduces the relationship between the result of changes in the quality of transport services, consumer utility of transport services and the level of resources used. Originality. The procedure for assessing the consumer utility of urban public passenger transport has been formalized, which, in contrast to the existing ones, is based on the established impact of technological parameters of routes on the formation of population mobility and ensures accounting of transport service quality indicators in determining the technological utility. Practical value. The application of the theory of utility in improving the operation of urban public passenger transport in general contributes to the development of the theory of passenger traffic management and can significantly increase the effectiveness of the choice of rational management measures to improve technological processes and the quality of transport services. The conditions for the formation of a positive impact of consumer utility of urban passenger transport on the mobility of the urban population are established. Based on the selected connection, it is possible to form a system of parameters for assessing the quality of public transport services.